Education and business requirements for the competencies and qualifications of modern tourism personnel; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Rodionova E. V. Elena Viktorovna; Zaviyalova Z. S. Zinaida Sergeevna; Baggio R. Rodolfo; Arlyapova P. A. (2016, 2016)
Title screen